The Evolving Role of Taxanes in Combination With Cetuximab for the Treatment of Recurrent and/or Metastatic Squamous Cell Carcinoma of the Head and Neck: Evidence, Advantages, and Future Directions - Guigay, Joël; Tahara, Makoto; Licitra, Lisa; Keilholz, Ulrich; Friesland, Signe; Witzler, Pauline; Mesía, Ricard (Frontiers in Oncology, 2019)
The addition of cetuximab to platinum-based chemotherapy (cisplatin or carboplatin plus 5-fluorouracil [5-FU]), followed by maintenance cetuximab until disease progression (EXTREME), resulted in the first regimen to yield significantly improved survival outcomes in the first-line treatment of patients with recurrent and/or metastatic squamous cell carcinoma of the head and neck (R/M SCCHN) in over 30 years. Currently, the EXTREME regimen is a guideline-recommended treatment in the first-line R/M setting, and, therefore, it is used as a control arm in all new first-line, phase 3 immunotherapy trials. More recently, new checkpoint inhibitor approaches have emerged and are changing the treatment landscape for PD-L1–positive patients with R/M SCCHN. Additionally, alternative chemotherapy backbones in R/M SCCHN are continually investigated. Replacing 5-FU with a taxane in the EXTREME regimen seeks to take advantage of the potential immunogenic and proapoptotic synergy between cetuximab and docetaxel or paclitaxel. These cetuximab-, platinum-, and taxane-based treatments have demonstrated promising survival results and cytoreductive properties in single-arm studies. Thus, these combination treatments may be of importance to patients with high tumor burden and dangerous site involvements (eg, causing bleeding, suffocation, dysphagia, or ulceration), in whom symptom relief is a key treatment goal. TPExtreme is the first large, randomized trial comparing a cetuximab, platinum, and taxane combination regimen with EXTREME. Currently, the substitution of 5-FU with a taxane is a feasible and clinically beneficial option for patients with contraindications to 5-FU. The TPEx regimen appears to be a new option in first-line R/M SCCHN, with a shorter time on CT and significantly lower toxicity than the EXTREME regimen. For patients with R/M disease in whom further cisplatin- or carboplatin-based treatment is unsuitable, or whose disease has already progressed on first-line R/M therapy, treatment options such as cetuximab plus a taxane, which capitalize on the combinative ability of the 2 agents, can be considered. Notably, it is as of yet unknown what second-line treatments may be suitable to follow a checkpoint inhibitor-based first-line therapy.